Evaluating chronic disease management Recommendations for funders and users - Nolte, Ellen (RAND Corporation, 2012)
This report outlines choices, options and trade-offs to policymakers, programme operators and researchers interested in the evaluation of chronic disease management. It is based on analyses undertaken within the DISMEVAL project.